Expression of Opacity Proteins Interferes with the Transmigration of Neisseria gonorrhoeae across Polarized Epithelial Cells. - Daniel C Stein (PLoS ONE, 2015)
Neisseria gonorrhoeae (GC) establishes infection at the mucosal surface of the human genital tract, most of which is lined with polarized epithelial cells. GC can cause localized as well as disseminated infections, leading to various complications. GC constantly change their surface structures via phase and antigenic variation, which has been implicated as a means for GC to establish infection at various anatomic locations of male and female genital tracks. However, the exact contribution of each surface molecule to bacterial infectivity remains elusive due to their phase variation. Using a GC derivative that is genetically devoid of all opa genes (MS11∆Opa), this study shows that Opa expression interferes with GC transmigration across polarized human epithelial cells. MS11∆Opa transmigrates across polarized epithelial cells much faster and to a greater extent than MS11Opa+, while adhering at a similar level as MS11Opa+. When MS11Opa+, able to phase vary Opa expression, was inoculated, only those bacteria that turn off Opa expression transmigrate across the polarized epithelial monolayer. Similar to bacteria alone or co-cultured with non-polarized epithelial cells, MS11∆Opa fails to form large microcolonies at the apical surface of polarized epithelial cells. Apical inoculation of MS11Opa+, but not MS11∆Opa, induces the recruitment of the Opa host-cell receptor carcinoembryonic antigen-related cell adhesion molecules (CEACAMs) to the apical junction and the vicinity of bacterial adherent sites. Our results suggest that Opa expression limits gonococcal ability to invade into subepithelial tissues by forming tight interactions with neighboring bacteria and by inducing CEACAM redistribution to cell junctions.